Translation, Cultural Adaptation, and Validation of the Multidimensional Scale of Perceived Social Support for Cancer Patients in Indonesia - Setiawan, Didik; Muamala, Anisa; Juwita, Dina Ratna; As Suaidy, Bustanuddin; Perwitasari, Dyah Aryani; Lianawati, Lianawati (Universitas Padjadjaran, 2022)
The social support is increasingly accepted as an important factor that influences the wellness of a human being, particularly people with chronic diseases. This study translates and validates the quantitative questionnaire that has been developed and has been widely accepted across cultures, namely the Multidimensional Scale of Perceived Social Support (MSPSS). The study was initially performed by translating the original questionnaire using forward and backward translation methods. Thirty cancer patients from Margono public hospital Purwokerto, Indonesia were conveniently included to evaluate the transleted questionmaire’s cconvergent, discriminant validity. Furthermore, 45 cancer patients were included in the main study which evaluate the level of social support among cancer patients. According to factor analysis, Kaiser-Meyer-Olkin Measure of Sampling Adequacy showed that the results is valid (0.668) while the Bartlett’s Test of Sphericity also showed that the number of samples were adequate (0.668) and eligible for factor analysis. The Measures of Sampling adequacy from each question was considerably higher than 0.5 and therefore there were no translated question that has to be removed in the analysis. There were 3 out of 12 factors that was included with the total variance of 81.166%. The Pearson’s correlation and Cronbach Alpha tests showed that discriminant validity and reliability test of the translated questionnaire were valid (>0.400) and reliable (>0.700) questionnaire. The translated version of the MSPSS was considerably a valid and reliable questionnaire to evaluate the level of social support for cancer patients in Indonesia.